Narratives of Al-Tabi’i Al-Aswad bin Yazid Al-Nakh’i (d. 75 AH) in Sunan Ibn Majah, an analytical study. (Journal of the College of Basic Education, 2022)
Imam al-Aswad bin Yazid al-Nakh’i (died 75 A.H.) drew the line of many narrators and imams of hadith, who had great merit in preserving the honorable Prophetic Sunnah and transmitting it to us, as well as preserving it from distortion and alteration, and for the importance of the Sunnah and the merit of the imams of hadith. Sunan Ibn Majah, may he benefit from it, Allah willing.